Homeland security preparedness and information systems strategies for managing public policy - Reddick, Christopher G. (Information Science Reference, 2010)
"This book examines the impact of Homeland Security Information Systems (HSIS) on government, discussing technologies used in a national effort to prevent and respond to terrorist attacks and emergencies such as natural disasters"--Provided by publisher.